Performance and Vibration Analyses of Lift-Offset Helicopters - Jeong-In Go; Do-Hyung Kim; Jae-Sang Park (International Journal of Aerospace Engineering)
A validation study on the performance and vibration analyses of the XH-59A compound helicopter is conducted to establish techniques for the comprehensive analysis of lift-offset compound helicopters. This study considers the XH-59A lift-offset compound helicopter using a rigid coaxial rotor system as a verification model. CAMRAD II (Comprehensive Analytical Method of Rotorcraft Aerodynamics and Dynamics II), a comprehensive analysis code, is used as a tool for the performance, vibration, and loads analyses. A general free wake model, which is a more sophisticated wake model than other wake models, is used to obtain good results for the comprehensive analysis. Performance analyses of the XH-59A helicopter with and without auxiliary propulsion are conducted in various flight conditions. In addition, vibration analyses of the XH-59A compound helicopter configuration are conducted in the forward flight condition. The present comprehensive analysis results are in good agreement with the flight test and previous analyses. Therefore, techniques for the comprehensive analysis of lift-offset compound helicopters are appropriately established. Furthermore, the rotor lifts are calculated for the XH-59A lift-offset compound helicopter in the forward flight condition to investigate the airloads characteristics of the ABC™ (Advancing Blade Concept) rotor.